Effect of alcohol use on the course of bipolar disorder: one‐year follow‐up study using the daily prospective Life Chart method. (27th March 2014) - van Zaane, Jan; van de Ven, Peter M; Draisma, Stasja; Smit, Johannes H; Nolen, Willem A; van den Brink, Wim
<x xml:space="preserve">Abstract</x> Objectives Relatively little is known about the temporal relationship between alcohol use and subsequent mood changes in patients with bipolar disorder, and the available findings are inconsistent. The present study was a fine‐grained analysis of the temporal relationship between alcohol use and short‐term mood‐switching probabilities. Methods The study included 137 patients with bipolar disorder who performed daily self‐ratings of their mood symptoms and the number of alcohol units consumed for a period of up to 52 weeks by using the National Institute of Mental Health self‐rated prospective Life Chart Method. At baseline, the Structured Clinical Interview for DSM‐IV was administered and demographic, social, and clinical characteristics were obtained. Multi‐state models were used to assess the impact of the number of alcoholic drinks on patients' transition through different states of mood (depression, euthymia, and mania). Results The effect of alcohol use on the change in mood states was limited. For women in a depressive state, higher alcohol use was associated with a shorter time before entering the euthymic state [hazard ratio (HR) = 1.18, 95% confidence interval (CI): 1.03–1.36, p < 0.05], whereas, for men in an euthymic state, higher alcohol use was associated with a longer time before entering a manic state (HR = 0.81, 95% CI: 0.71–0.92, p < 0.05). The correlation between the consumed number of drinks per week and the average mood severity score of the following week was −0.01 (p < 0.001), indicating that only 0.01% of the variance in mood severity in this population is explained by alcohol use. Possible explanations for these findings are discussed. Conclusions The current study, using a fine‐grained analysis, suggests that alcohol use does not have a direct effect on the course of bipolar disorder in patients using mood stabilizers.